Da Vinci's Mona Lisa Entering the Next Dimension. (August 2013) - Carbon, Claus-Christian; Hesslinger, Vera M
For several of Leonardo da Vinci's paintings, such as The Virgin and Child with St Anne or the Mona Lisa, there exist copies produced by his own studio. In case of the Mona Lisa, a quite exceptional, rediscovered studio copy was presented to the public in 2012 by the Prado Museum in Madrid. Not only does it mirror its famous counterpart superficially; it also features the very same corrections to the lower layers, which indicates that da Vinci and the 'copyist' must have elaborated their panels simultaneously. On the basis of subjective (thirty-two participants estimated painter-model constellations) as well as objective data (analysis of trajectories between landmarks of both paintings), we revealed that both versions differ slightly in perspective. We reconstructed the original studio setting and found evidence that the disparity between both paintings mimics human binocular disparity. This points to the possibility that the two Giocondas together might represent the first stereoscopic image in world history.